IBM PASAR SAMPANGAN BARU SEMARANG - Indriyanti, Dyah Rini; Banowati, Eva; Margunani, Margunani (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
IbM activities carried out in Sampangan Pasar Baru, Jalan Raya village Bendan Menoreh Duwur, District Gajahmungkur Semarang. The purpose of these service activities, namely: 1) train KSM Pasar Baru Sampangan process organic waste into organic fertilizer ready for sale. 2) help the government tackle the waste problem by creating a model of market-based processing of organic waste. 3) educate the traders of vegetables in order to dispose of waste in place and sort out organic and non-organic. There are two groups who are partners, namely: the first group of traders, especially traders vegetables every day produces organic and non-organic waste amounts to approximately 75 merchants. The second group of organic waste processing. IbM devotion steps that have been made are as follows: socialization and coordination of relevant parties, the manufacture of home composting, procurement of equipment and materials, training composting, educating the traders to dispose of waste in place, processing of organic waste regularly. Results obtained: 1) KSM Market Sampangan New’ve processing organic waste market becomes compost and is already on sale, 2) Produced SDM many as three people from KSM Market Sampangan New that can process organic waste market into compost, 3) Traders vegetables approximately 75% were taking out the trash in place, although not entirely sorted garbage sorting.